Growth and productivity characterization of young teak (Tectona grandis Linn f.) plantations and estimation of site index curves in the septentrional area of the Republic of Guatemala - Mollinedo García, Manuel Sabino; Herrera Machuca, Miguel Ángel; Muñoz Sáez, Fernando (Instituto de Ecología, A.C., 2016)
In 2015 the teak (Tectona grandis Linn f.) plantations of Guatemala covered approximately 33 000 hectares, of which 80% are located in the septentrional northern region and, in order to characterize the evolution in terms of growth and development, data from a total of 248 permanent monitoring plots (in plantations established between 1998 and 2001 with measurements each year between 2004 and 2009) have been analyzed. The results show that, on average, 13,01% of the sites present high growth, 70,66% medium growth and 16,33% low growth. For the sites of medium to high growth, i.e., 83,67 %, the Site Index at a base age of 10 years that will be achieved will be between 19,13 m and 25,32 m, a mean annual increase in total height (MAIHTOT) of between 1,98 m yr-1 and 2,62 m yr-1, a mean annual increase in DBH (MAIDBH) of between 2,23 cm yr-1 and 2,82 cm yr-1 and productivity (MAIVOL) of 9,89 m3 yr-1 to 17,22 m3 yr-1. The sites that present low growth rates will reach a site index of 12,94 m, a MAIHTOT of 1,34 m yr-1, a MAIDBH of 1,65 cm yr-1 and a maximum productivity of 2,55 m3 yr-1. The analysis of variance showed significant differences with a p-value ≤ 0,001 in site index, MAIHTOT, MAIDBH, MAIBA and MAIVOL. The site index curves based on a modified growth model allowed the identification and definition of a land classification based on its productive capacity on site, and thus evidences the growth and development of teak in Guatemala.